Neoadjuvant Four-Drug Combination Therapy for NSCLC With EGFR Mutation Avoiding Total Pneumonectomy - Li, Jingpei; Xu, Ke; Cai, Weipeng; Zhang, Yalei; Zeng, Xin; Cui, Fei; Hao, Zhexue; Liu, Jun; He, Jianxing (Frontiers in Oncology, 2020)
We report a case of successful neoadjuvant four-drug combination therapy to avoid total pneumonectomy. A 33-year-old male patient was diagnosed with locally advanced non-squamous NSCLC harboring EGFR mutation in the left lower lobe. The patient experienced significant clinical downstaging after two cycles of neoadjuvant therapy, including icotinib, carboplatin, pemetrexed, and bevacizumab. He underwent a successful lobectomy avoiding pneumonectomy. The patient showed no recurrence in the follow-up of a chest computed tomographic scan, which is 17 months after surgery. The promising results of this neoadjuvant combination therapy provided a novel therapeutic option for patients with locally advanced EGFR-mutated NSCLC facing total pneumonectomy.